Performance of Health Workers at XYZ Hospital with Job Satisfaction as a Mediating Variable - Setiawan, Iwan; Meilani, Yohana F. Cahya Palupi (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of job satisfaction on the performance of health workers at XYZ Hospital, with the variables of leadership, organizational culture and organizational support as independent variables. The population in this study were all health workers who worked for at least one year at XYZ Hospital. The sampling technique was determined by using the purposive sampling method. PLS-SEM data analysis technique using analysis software SmartPLS version 3.0. The results of this study indicate that H1 leadership has a positive and significant effect on job satisfaction. H2 organizational culture has a positive and significant effect on job satisfaction. H3 organizational support has a positive and significant effect on job satisfaction. H4 job satisfaction has a positive and significant effect on performance.